A strategy for research in space biology and medicine in the new century (National Academy Press, 1998)
The Committee on Space Biology and Medicine reviewed and updated prior reports to suggest strategies for research in space biology and medicine based on information gathered since 1987. The report provides a review of biology and medicine that can be studied in the space environment, discusses the fundamental research issues and questions with space biology and medicine disciplines, identifies the most promising experimental challenges in those disciplines, evaluates the potential for space research to provide advances within each discipline, and prioritizes research topics to the extent feasible. Disciplines include sciences which study plant, animal, and human systems at the molecular, cellular, system, and whole-organism levels. The section about physiology, gravity, and space includes cell biology; developmental biology; plants, gravity, and space; sensorimotor integration; bone physiology; skeletal muscle; cardiovascular and pulmonary systems; endocrinology; and immunology. The section about additional space environment issues includes radiation hazards and behavioral issues. The final section examines setting priorities in research and programmatic and policy issues.